Satisfaction Level of Periodontitis Patients with Teeth Luxation Post Splinting Treatment at RSGM UMY - Hartanti Hartanti; Riska Fitri Febriyanti (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Periodontal disease is one of the global oral health problems. Periodontitis is still the leading cause of tooth loss in adults worldwide. Periodontitis may cause discomfort related to tooth loss during eating. Loss of teeth, either one or several teeth, can cause functional and aesthetic disturbances that can affect a person's level of satisfaction. There are several treatments to treat tooth loss, one of which is splinting treatment. Splinting is a therapy that connects several teeth to increase the stability of the teeth due to periodontitis. This study aims to describe the level of satisfaction of patients with periodontitis with tooth luxation after splinting at the Dental Hospital of Universitas Muhammadiyah Yogyakarta (RSGM UMY). This research method is descriptive observational, with a total sample of 38 respondents. The sample inclusion criteria were all patients who had splinting done by a Co-Ass at RSGM UMY and all patients who had splinting done by a Co-Ass at RSGM UMY with a tooth luxation degree 2. The sample exclusion criteria were patients who were not willing to be respondents. The study's results showed that 26.95% of patients were very satisfied, 62.63% were satisfied, 8.74% were not satisfied, 1.47% were dissatisfied, and 0.21% were very dissatisfied. The satisfaction level of periodontitis patients with teeth luxation post splinting treatment at RSGM UMY in all five dimensions was in the ‘satisfied’ category with a percentage of 62.63%.